2016
DOI: 10.4046/trd.2016.79.4.234
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Infection Control in Health-Care Facilities: Environmental Control and Personal Protection

Abstract: Transmission of tuberculosis (TB) is a recognized risk to patients and healthcare workers in healthcare settings. The literature review suggests that implementation of combination control measures reduces the risk of TB transmission. Guidelines suggest a three-level hierarchy of controls including administrative, environmental, and respiratory protection. Among environmental controls, installation of ventilation systems is a priority because ventilation reduces the number of infectious particles in the air. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
0
29
0
2
Order By: Relevance
“…Airborne diseases have been linked to poorly functioning HVAC system: improper function of temperature control, humidity control, air distribution and filtration of HVAC systems [16][17][18][19][20][21][22][23][24][25][26][27][28]. Lutz et al reported an outbreak of Aspergillus infection among inpatients who had been operated in the same operating room in a 12-day period.…”
Section: Clinical Importance Of Hvac Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Airborne diseases have been linked to poorly functioning HVAC system: improper function of temperature control, humidity control, air distribution and filtration of HVAC systems [16][17][18][19][20][21][22][23][24][25][26][27][28]. Lutz et al reported an outbreak of Aspergillus infection among inpatients who had been operated in the same operating room in a 12-day period.…”
Section: Clinical Importance Of Hvac Systemmentioning
confidence: 99%
“…Lee suggested that diseases like tuberculosis require 'threelevel' hierarchy to control the spread of disease in hospitalized patients: first, medical-administrative role in early diagnosis, isolation and treatment; second, environmental aspect by reducing the concentration of airborne bacilli by increasing number of air changes per hour (ACR) and single-pass ventilation systems where 100% supplied air is exhausted to avoid re-circulation; and the third level, being the use of personal protective equipment [25].…”
Section: Clinical Importance Of Hvac Systemmentioning
confidence: 99%
“…La prueba de ajuste es una de las estrategias que permite evaluar la capacidad de hermeticidad entre los bordes del respirador N95 y la superficie facial del TS para identificar fugas; se mide a trav茅s del factor de ajuste expresado como la relaci贸n entre la concentraci贸n de part铆culas en el ambiente y las encontradas al interior del respirador; un valor mayor o igual a cien significa que el respirador tiene un adecuado ajuste a la cara del trabajador, por ende, este valor se constituye en un factor protector que disminuye el riesgo de penetraci贸n de part铆cu-las pat贸genas que puedan ser inhaladas (31,32). Por tanto, la prueba de ajuste proporciona un medio para determinar el modelo y el tama帽o del respirador que se ajusta mejor al TS as铆 como para comprobar y evaluar la postura correcta del respirador (33).…”
Section: Pruebas De Ajuste Del Respirador N95unclassified
“…[12] It is advisable that patients with suspected or confirmed pulmonary TB be isolated in a single room with negative pressure and en suite facilities. [13] This is, however, not always possible. Where negative pressure facilities are not available, natural ventilation can be an effective and cost-efficient way of ensuring adequate air mixing.…”
mentioning
confidence: 99%